Prosedur Penyusunan Anggaran Biaya Operasional pada Kantor Balai Pengkajian Teknologi Pertanian Provinsi Aceh - Ermila; M Djamil HS (Yayasan Kawanad, 2022)
This research analyzes the procedures for preparing operational budgets at the Aceh Province Agricultural Technology Assessment Center Office. With a qualitative approach, the participation of financial staff, managers, and organizational leaders involves in-depth interviews, observations, and document analysis. The results show a lack of involvement of related parties, suboptimal utilization of technical broadcasting, challenges in estimating factory overhead costs, untimely decision-making, and a lack of integration of financial information systems. The discussion suggested strategic improvements, such as increased engagement, optimization of forecasting, handling of overhead cost estimates, increased responsiveness of decision-making, and investment in information integration systems. In conclusion, corrective action is needed to achieve effectiveness and efficiency in preparing operational cost budgets